Working experiences of nurses during the novel coronavirus outbreak: A qualitative study explaining challenges of clinical nursing practice - Fatmah Alsolami (Wiley, 2022)
Abstract Aim To explore the clinical working experiences of Saudi nurses during the novel Coronavirus outbreak, identify the challenges and determine how these challenges affect their nursing practice. Background From the current experience of working during the novel Coronavirus outbreak, it is statistically significant to identify the challenges that nurses in Saudi Arabia face in their clinical practice and determine how these challenges affected their practice. Designs A qualitative descriptive study. Methods An in‐depth interview with eight Registered Nurses in Saudi Arabia who worked in areas where the novel Coronavirus patients are treated were conducted between 10 and 23 April. Results The following eight major themes were identified from this study: physical exhaustion, fear of infection, providing care with uncertainty, uncomfortable use of personal protective equipment, missed nursing care, prolonged procedures, lack of guidance during the outbreak and lack of managerial support. Conclusion The results suggest that nurses' leaders should take active roles in empowering nursing staff. The absence of direct monitoring for nursing performance during their practice compromises patient safety and jeopardises the quality of care through missed nursing care. This study also revealed that nurses who worked during the outbreak need psychological support that can enhance their emotional resilience.